1950
DOI: 10.1001/jama.1950.02910230006002
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm of the Intracranial Carotid Artery

Abstract: ondary inflammatory changes. Total removal of the lung may be required if resection is attempted, and when a small intrabronchial tumor is responsible for the entire process pneu¬ monectomy seems unjustifiably destructive. I believe that moderate infection distal to the tumor is not justification for removing portions of the lung. After the removal of an obstruc¬ tion, such as a foreign body, the lung has extraordinary reparative power, and in many patients the infection may disappear completely. I would like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1950
1950
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There have been a few descriptions of the effects of carotid ligation on aneurysm induced palsies (Jefferson, 1967;Hamilton and Falconer, 1959;Cantu, 1969;Hepler and Cantu, 1969;Raja, 1972) and brief mention of the results after direct intracranial approach to the aneurysm (Jaeger, 1950;Henderson, 1955;Harris and Udvarhelyi, 1957;Botterell et al, 1962;Johnston and Pratt-Johnson, 1963), but in many of these cases it is impossible to correlate the site of the aneurysm with the type of treatment carried out. Jefferson (1947) found that the palsy never recovered fully, but Jaeger (1950) stated that, even if the third nerve were seriously withered by pressure, it could still recover completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few descriptions of the effects of carotid ligation on aneurysm induced palsies (Jefferson, 1967;Hamilton and Falconer, 1959;Cantu, 1969;Hepler and Cantu, 1969;Raja, 1972) and brief mention of the results after direct intracranial approach to the aneurysm (Jaeger, 1950;Henderson, 1955;Harris and Udvarhelyi, 1957;Botterell et al, 1962;Johnston and Pratt-Johnson, 1963), but in many of these cases it is impossible to correlate the site of the aneurysm with the type of treatment carried out. Jefferson (1947) found that the palsy never recovered fully, but Jaeger (1950) stated that, even if the third nerve were seriously withered by pressure, it could still recover completely.…”
Section: Discussionmentioning
confidence: 99%
“…Jefferson (1947) found that the palsy never recovered fully, but Jaeger (1950) stated that, even if the third nerve were seriously withered by pressure, it could still recover completely. Henderson (1955) said that the paralysis had cleared completely in 11 of 23 patients, and Botterell et al (1962) found that, of 28 patients who had a craniotomy, eight had complete recovery of third nerve function but, of eight who had a carotid ligation, all had residual defects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact Jaeger, in an analysis of 31 cases of intracranial carotid aneurysms, found that the combined symptoms of oculomotor paresis associated with frontal or orbital head pains are sufficient to permit a presumptive diagnosis of aneurysm. 9 Epistaxis, however, is not considered a classic symptom of intracranial aneurysm. Still, this rare presentation can be a conspicuous feature of these aneurysms.…”
Section: Discussionmentioning
confidence: 99%